Motivations and strategies for changing the current family laws in Pakistan: پاکستان میں رائج الوقت عائلی قوانین میں تبدیلی کےلئے محرکات و لائحہ عمل - Akram, Dr. Nighat; Malik, Majid Nawaz (Al Khadim Research Journal of Islamic Culture and Civilization, 2022)
Family law has been one of the most politically and socially queried issues in Muslim frameworks in the current period. This has had both positive and negative aspects. On the one hand, it has opened up the possibility of discussing matters and power relationships previously regarded as strictly belonging to the private circle but on the other hand most prevalent areas of discrimination against women in the Muslim world today is the inequality that occurs within the context of the family law. Throughout Muslim countries, Muslim women are fighting for reform of family laws to promote justice and equality within the family. This paper explores the demand for positive change in family laws and for the protection of rights, explaining ways in which equality and justice in the Muslim family have become increasingly possible .After citing examples of the vast diversities in legal systems and laws relating to families in Muslim countries, the paper outlines a variety of strategies used by activists to promote equality and justice in family laws. Available case studies demonstrate the challenges women today face within Muslim families and societies, and show how women and whole nations have come together to overcome these challenges by making legal and policy breakthroughs to better assurance justice and equality for all. All in all, these realities compel us to acknowledge that gender equality and justice in the Muslim family have become undeniable necessities and that, through educated political leadership, vibrant democratic processes, and the hard struggles of Muslim women and their supporters, their fulfillment is possible.